Analisis Hubungan Turnover Intention dan Beban Kerja pada Karyawan Logistik: Peran Work-Life Balance sebagai Mediator di PT. Wahana Lintas Nusantara - Eka Putri Prinanda Nitte; Nurul Karimah; Siti Mujanah; Achmad Yanu Alif Fianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the relationship between workload and turnover intention among logistics employees at PT. Wahana Lintas Nusantara, as well as to examine the role of work-life balance as a mediator in this relationship. The sample consists of 150 employees working in the company's logistics department. Data were analyzed using Structural Equation Modeling (SEM) to test the relationships between variables, considering both direct and indirect effects. The results show that workload has a positive and significant effect on turnover intention (path coefficient = 0.45, p < 0.05), indicating that the higher the workload, the greater the likelihood of employees intending to leave the job. Furthermore, work-life balance was found to serve as a significant mediator in this relationship, with an indirect effect of 0.27 (p < 0.01). These findings suggest that an imbalance between work and personal life can exacerbate the negative impact of workload on turnover intention. Demographic factors, such as age and tenure, also influence turnover intention, with younger employees and those with shorter tenure being more likely to have higher turnover intentions. This study provides insights for companies to manage workload effectively and support work-life balance as strategies to improve employee retention and reduce turnover intention.